2021
DOI: 10.1001/jamainternmed.2020.5519
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Overcorrection in Rapid Intermittent Bolus vs Slow Continuous Infusion Therapies of Hypertonic Saline for Patients With Symptomatic Hyponatremia

Abstract: IMPORTANCEFew high-quality studies have clarified whether hypertonic saline is best administered as slow continuous infusion (SCI) therapy or rapid intermittent bolus (RIB) therapy for symptomatic severe hyponatremia.OBJECTIVE To compare the risk of overcorrection in RIB and SCI with hypertonic saline in patients with symptomatic hyponatremia. DESIGN, SETTING, AND PARTICIPANTS This prospective, investigator-initiated, multicenter, open-label, randomized clinical trial enrolled 178 patients older than 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
73
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 49 publications
0
73
0
3
Order By: Relevance
“…Therefore, we believe that it may be better not to recommend an immediate second bolus of 150 mL 3%NaCl but instead rely on clinical presentation and decide about treatment intensification sometimes later. Neurologic outcome was also not different in the trial from Garrahy et al and in the SALSA trial although sodium increased faster in the bolus groups of both trials ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, we believe that it may be better not to recommend an immediate second bolus of 150 mL 3%NaCl but instead rely on clinical presentation and decide about treatment intensification sometimes later. Neurologic outcome was also not different in the trial from Garrahy et al and in the SALSA trial although sodium increased faster in the bolus groups of both trials ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 67%
“…The recently published prospective multicentric randomized SALSA trial compared weight adjusted hypertonic saline bolus with a slow continuous hypertonic saline infusion in symptomatic hyponatremia. This study found that hypertonic boluses were superior in achieving the targeted increase in sNa without exposing patients to a higher overcorrection rates ( 15 ). Bolus therapy required less relowering interventions compared to the continuous infusion ( 15 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…American and European guidelines have recommended administering hypertonic saline in small, fixed boluses based on low-quality evidence from small randomized trials and expert opinions [ 1 , 5 , 6 ]. Recently, efficacy and safety of rapid intermittent correction vs slow continuous correction with hypertonic saline in patients with symptomatic hyponatremia: a randomized clinical trial (SALSA trial) involving patients from three general hospitals in Korea from 2016 to 2019 has investigated the efficacy and safety of rapid intermittent bolus (RIB) compared with slow continuous infusion (SCI) with hypertonic saline [ 7 ]. This study aimed to introduce the results of the SALSA trial and discuss a bolus regimen of hypertonic saline as an optimal treatment in patients with symptomatic hyponatremia.…”
mentioning
confidence: 99%
“…We recommend rapid intermittent bolus correction as shown in Fig. 1 [ 1 , 5 , 7 ]. First, patients should be classified into two groups based on severity of hyponatremia: moderately severe (nausea, headache, drowsiness, general weakness, and malaise) and severe (vomiting, stupor, seizure, and coma [Glasgow coma scale, ≤ 8]) symptomatic hyponatremia.…”
mentioning
confidence: 99%